First Report of the L925I kdr Mutation Associated with Pyrethroid Resistance in Genetically Distinct Triatoma dimidiata, Vector of Chagas Disease in Mexico - Mario C. Saucedo-Montalvo; Jesus A. Davila-Barboza; Selene M. Gutierrez-Rodriguez; Beatriz Lopez-Monroy; Susana Favela-Lara; Iram P. Rodriguez-Sanchez; Guadalupe del C. Reyes-Solis; Cristina Bobadilla-Utrera; Adriana E. Flores (Tropical Medicine and Infectious Disease, 2025)
Triatoma dimidiata is a widely distributed vector of Trypanosoma cruzi in Mexico and Central America, found across a range of habitats from sylvatic to domestic. Vector control has relied heavily on indoor residual spraying with pyrethroids; however, reinfestation and emerging resistance have limited its long-term effectiveness. In this study, we analyzed the genetic diversity and population structure of T. dimidiata from Veracruz, Oaxaca, and Yucatan using mitochondrial markers (cyt b and ND4) and screened for knockdown resistance (kdr)-type mutations in the voltage-gated sodium channel (VGSC) gene. High haplotype diversity and regional differentiation were observed, with most genetic variation occurring between populations. The ND4 marker provided greater resolution than cyt b, revealing ten haplotypes and supporting evidence of recent population expansion. Haplotype networks showed clear geographic segregation, particularly between populations east and west of the Isthmus of Tehuantepec. The L925I mutation, highly associated with pyrethroid resistance, was detected for the first time in Mexican populations of T. dimidiata, albeit at low frequencies. These findings highlight the importance of integrating population genetic data and resistance surveillance into regionally adapted vector control strategies for Chagas disease.